Quality of Chilled Ram Semen in Tris Egg Yolk Extender Added with Different Concentrations of Glutamine: Quality of Chilled Ram semen in extender added with glutamine - Aisyah Fidela Siregar; Mokhamad Fahrudin; Ni Wayan Kurniani Karja; Wahono Esthi Prasetyaningtyas (Hasanuddin University, 2023)
Glutamine is a non-essential amino acid that can reduce free radicals and act as an antioxidant. This study aims to determine the effect of adding glutamine in egg yolk tris diluent at concentrations of 0 mM (K), 2,5 mM (G2,5), 5 mM (G5), and 7,5 mM (G7,5) on the quality of liquid semen and kept in a refrigerator at 4 °C. Microscopic evaluation was performed immediately after dilution (H0) and every 24 hours until day 5 (H5). The results showed that the G 7,5 mM group could maintain better motility and viability (P < 0,05) than the K, G 2,5, and G 5 groups. The addition of glutamine did not have a significant effect (P> 0.05) in maintaining the MPU of spermatozoa. Glutamine with a concentration of 7.5 mM is the best concentration to maintain the quality of sheep's liquid semen.